The Effect of Halal Literacy and the Burden of Management Costs on the Interest of MSMEs in the Halal Certification Process - Abdul Hadi Ismail; Sariyanto; Riyan Pradesyah; Munawaroh Munawaroh (Universitas KH. Abdul Chalim Mojokerto, 2026)
The low level of halal certification ownership among Micro, Small, and Medium Enterprises (MSMEs) remains a significant issue amidst the increasing market demand for halal products. This issue is thought to be influenced by low halal literacy among business actors and their perceptions of the cost burden of halal certification processing. This study aims to analyze the influence of halal literacy and the cost burden of processing on MSMEs' interest in the halal certification process in Medan City. This study uses a quantitative approach with a survey method. Data collection was conducted through the distribution of online questionnaires using Google Forms to MSMEs in Medan City. The data obtained were then tabulated and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method through the SmartPLS application. The analysis includes testing the measurement model (validity and reliability) and the structural model to examine the relationship between variables. The results show that halal literacy has a positive and significant effect on MSMEs' interest in processing halal certification. This indicates that the higher the level of understanding of MSMEs regarding the halal concept and the benefits of certification, the greater their interest in participating in the halal certification process. On the other hand, the burden of administrative costs does not have a significant effect on the interest of MSMEs, which shows that the cost factor is not a primary consideration in business actors' decision-making.